How Can We Strengthen Governance of Non‐communicable Diseases in Pacific Island Countries and Territories?. Issue 2 (19th May 2015) - Magnusson, Roger S.; Patterson, David
Abstract: Pacific island countries and territories (PICTs) are some of the most geographically isolated in the world. Most have small populations and economies. In addition to the economic challenges that they face because of isolation and size are the risks of climate disaster and the challenge of non‐communicable diseases (NCDs), including cardiovascular disease, cancer, diabetes and tobacco‐related diseases. This article builds on knowledge about the key features that characterise effective national responses to NCDs, as embodied in the World Health Organization's Global Action Plan for the Prevention and Control of Noncommunicable Diseases 2013–2020. It seeks to identify some promising strategies for strengthening the governance and law reform processes that will be required to enhance the capacity of small island states to reduce NCD risks in their populations.